Charting the Course: Strategic Planning for Knowledge Mobilization in Research-Intensive Universities - MacGregor, Stephen; Maduforo, Aloysius; Coombs, Emily; Fedorko-Bartos, Kristi-Mari (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
This study examines the strategic knowledge mobilization (KMb) planning resources employed by research-intensive universities. Focusing on four universities that participate in a professional network dedicated to KMb, the analysis identifies distinctive approaches to KMb, highlighting key features such as impact assessment, global challenge alignment, knowledge exchange, and needs-based infrastructure development. Key differences across the institutions include the specificity of implementation plans, the degree of stakeholder engagement, and the strategic use of resources. Drawing on resource-based view, institutional theory, and social learning theory, this study underscores the importance of tailoring KMb strategies to local contexts while leveraging broader institutional goals and theoretical perspectives. These findings offer valuable insights for university administrators and emphasize the need for further research to build an evidence base for KMb and to strategically integrate it into core institutional functions for addressing complex societal challenges.